SINTESIS KOMPOSIT NANO PANI/Fe3O4 KONDUKTIF BERBASIS PASIR ALAM - Hamid, Abd Basith; Sholichah, Nikmatin; Rahayu, Vira; Ardimas, Ardimas; Fadhli, Ulfa Mahfudli (Universitas Mataram, 2021)
Polyaniline is a polymer material that has unique physical and even chemical properties, especially in its electrical properties. PANi synthesis can be carried out by chemical and electrochemical oxide reaction methods. The purposes of this study are to synthesize PANi and PANi / Fe3O4 composites by chemical oxide reactions and measure their conductivity. This research begins with the synthesis of iron oxide (Fe3O4) from natural iron sand and then followed by the synthesis of PANi / Fe3O4 composites using copreticipitation method. The Fe3O4 crystal phase was determined by using XRD, while the vibrational mode and morphology of the PANi / Fe3O4 nanocomposite was observed using FTIR and SEM. The conductivity properties were measured using a LCR meter. Furthermore, the conductivity properties were measured using a LCR meter and the result reveals a greater conductivity value as increasing the concentration of Fe3O4, the highest conductivity value of 3.1 mS/cm is known by the sample with an iron oxide concentration of 1 %. While the samples with a concentration of 0.5 % of iron oxide has conductivity valuesÂ of 2.8 mS/cm and pure PANi of 2.1 mS/cm. Due to its properties such Â to inert to the environment and having conductive properties, the obtained PANI / Fe3O4 composite can be employed as a super capacitor electrode.